Effect of swelling on fatigue life of elastomers. (February 2016) - Loo, M.S.; Le Cam, J.B.; Andriyana, A.; Robin, E.; Coulon, J.F.
Abstract: In a number of engineering applications, elastomeric components are exposed to aggressive solvent such as biodiesel. Since biodiesel is considered as a potential substitute for conventional fossil fuel, the study on the durability in service of elastomers exposed to biodiesel becomes essential. The present paper investigates the mechanical response of swollen elastomers, due to exposure to palm biodiesel, under fatigue loading conditions. To this end, fatigue tests are conducted on dry and swollen rubber specimens at various maximum strains and a zero strain ratio. The physical fatigue damage mechanism induced in swollen material is studied through FESEM analysis coupled with EDS. During the test, two definitions of specimen end-of-life are adopted: (i) the number of cycles required for a nucleated crack to reach 1 mm in length and (ii) the number of cycles required for a complete rupture to occur in the specimens. The fatigue lifetime curves are plotted where the maximum principal stretch is used as the predictor. It is shown that swollen rubbers have shorter lifetime compared to the dry ones. Moreover, FESEM results reveal that the swelling level has no effect on the morphology of crack nucleation and propagation, regardless of the imposed loading level.